2022
DOI: 10.3390/agriculture12091481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Nutrient Contents and Nutritive Value of Taif’s Rose (Rosa damascena Mill var. trigintipetala) Waste to Be Used as Animal Forage or Soil Organic Fertilizers

Abstract: This study aimed to evaluate the nutrient content and nutritive value of pruning waste of the Taif Damask rose for its potential use as an organic fertilizer or animal forage in the Taif region, Saudi Arabia. For this purpose, the pruning waste of Taif’s rose and soil samples supporting the plant growth at different ages were collected from four farms (F1: 4, F2: 10, F3: 12, and F4: 20 years old). The total aboveground biomass (AGB) of the plants, stems, and leaves were measured in addition to the stem height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…The nutritional value of TR plant parts was lower than that found in herbal plant residues and olive mill waste ( [68,69], respectively). The current study is in line with the findings of Galal et al [17], who found that the macronutrient content of TR leaf and stem pruning wastes makes them more promising for composting in order to improve soil quality than flowers and SDW. The various plant organs of TR can be used as additives in organic fertilizers because their nutrient release rate is too slow to meet crop requirements in a timely manner.…”
Section: Mineral Nutrientssupporting
confidence: 92%
See 4 more Smart Citations
“…The nutritional value of TR plant parts was lower than that found in herbal plant residues and olive mill waste ( [68,69], respectively). The current study is in line with the findings of Galal et al [17], who found that the macronutrient content of TR leaf and stem pruning wastes makes them more promising for composting in order to improve soil quality than flowers and SDW. The various plant organs of TR can be used as additives in organic fertilizers because their nutrient release rate is too slow to meet crop requirements in a timely manner.…”
Section: Mineral Nutrientssupporting
confidence: 92%
“…In addition, the plant leaves had the highest contents of P and Ca (6.58 ± 0.54 and 173.93 ± 26.03 mg kg −1 , respectively) but the lowest of K and Mg (101.54 ± 10.89 and 85.43 ± 14.90 mg kg −1 , respectively). The values of these elements (except K, P, and Ca) were lower than those recorded in the leaf and stem pruning wastes of the same species [17]. Moreover, the highest Na content (198.08 ± 12.34 mg kg −1 ) was recorded in the flower tissues, which was comparable to 195.18 ± 9.32 mg kg −1 recorded in the SDW.…”
Section: Mineral Nutrientsmentioning
confidence: 63%
See 3 more Smart Citations